Genetic Ablation of the Inducible Form of Nitric Oxide in Male Mice Disrupts Immature Neuron Survival in the Adult Dentate Gyrus - Fernandes, Gabriel G.; Costa, Karla C. M.; Scomparin, Davi S.; Freire, Juliana B.; Guimarães, Francisco S.; Campos, Alline C. (Frontiers in Immunology, 2021)
Inducible nitric oxide synthase (iNOS) is an enzyme upregulated in the brain during neuroimmune responses associated with an oxidative and pro-inflammatory environment in several brain regions, including the hippocampus. Besides, this region still generates new neurons during adulthood, process known as adult hippocampal neurogenesis (AHN). Although many factors modulate AHN, the exact participation of specific proinflammatory mediators such as iNOS the proliferation, differentiation, migration, and cell survival in this process remains to be fully understood. Here, we investigated the behavioral effects and hippocampal neurogenic niche changes of iNOS knockout (K.O.) mice submitted to chronic unpredictable stress (CUS - 21 days protocol). Contrary to our initial hypothesis, at control conditions, iNOS K.O. mice displayed no abnormalities on microglial activation in the dentate gyrus. However, they did exhibit impaired newborn cells and immature neuron survival, which was not affected by CUS. The reduction of AHN in iNOS K.O. mice was accompanied by an increased positive coping response in the tail suspension test and anxiety-like behaviors in the novelty suppressed feeding. The CUS protocol did not influence the behaviors displayed by iNOS K.O. mice at control conditions. Next, we investigated whether a pro-neurogenic stimulus would rescue the neurogenic capacity of iNOS K.O. mice by administering in control and CUS groups the antidepressant escitalopram (ESC). The chronic treatment with ESC could not rescue the neurogenic capacity or the behavioral changes observed in the control groups of the iNOS K.O. mice. Next, we evaluated the neuronal activation with FOSB (a marker of chronic cell activity) and the expression of parvalbumin-positive interneurons (PV) in the ventral medial prefrontal (vmPFC), another brain region also affected by pro-inflammatory mediators and stress responses. There was no change in the expression or the chronic activation of PV neurons (evaluated by double labeling PV with FOSB) in the prelimbic (PrL) or infralimbic vmPFC. FOSB expression, however, increased in the PrL of iNOS K.O. mice. Our results suggest that iNOS seems essential for the survival of newborn cells and immature neurons in the hippocampus. In addition, the lack of this enzyme appears to result in increased activity of the PrL prefrontal cortex.